Globalization and its Transformations in Contemporary ceramics (European and American Porcelain a Model): أسعد مطر خليل (Al-Academy, 2019)
Globalization has occupied a great deal of studies, research and literature, in addition to being a phenomenon that has imposed itself firmly on the ground. Globalization is considered the main feature of the current moment in today's world. The world is now transforming in an unprecedented way under noticeable titles of successive waves of knowledge and technology.The current research aims to identify the effects of globalization on the variables and their political, social, media and cultural dimensions, as well as culture of consumption and cultural identity.The theoretical framework included two sections: the first is the concept of globalization, its history and its dimensions, and the second is the modernity in contemporary European and American porcelain. The research procedures included the selection of the research community, the sample, and the sample classification tool and then the analysis of the samples. The researcher presented the findings and conclusions and then put forth a set of recommendations and proposals, and concluded the research with a list of indexes, sources and references